How weight and body size affect learning: a qualitative exploration of experiences in secondary school. (November 2021) - Langford, Rebecca; Davies, Alisha; Howe, Laura; Cabral, Christie
Abstract: Background: Being above a healthy weight is associated with lower academic achievement. Various explanations have been put forward to explain this association, but evidence for causal pathways is sparse and unclear. This study sought to qualitatively explore the association between bodyweight, body size, and learning. Methods: We interviewed 19 adults (late 20s; 14 women, five men) and one young person (14 years, male) from the UK in 2019–20. Ethnicity was not formally recorded. Adult participants were recruited from the ALSPAC 1990s birth cohort, sampled to ensure diversity in socioeconomic status and educational attainment; the teenage participant was recruited from a youth community-based weight management group. Interviews focused on experiences of being above a healthy weight (self-identified) during secondary school and on how this bodyweight might have affected their learning and achievement. Interviews were face-to-face, digitally recorded, and transcribed verbatim. We analysed the data thematically to create three key themes linked within a theoretical model. Ethics approval for this study was obtained from the ALSPAC Ethics and Law Committee (86964) and the Faculty of Health Sciences Research Ethics Committee (85702) at the University of Bristol Findings: Because a larger body size is highly stigmatised, all participants engaged in different strategies to minimise their exposure to negative attention. Participants sought to either increase their social acceptance or become less socially visible (or a combination of both). Three participants appeared to navigate this experience successfully: they had many friends (or the right friends), experienced little or no bullying at school, and weight appeared to have little effect on their achievement at school. For most, however, school was a negative social environment, and the behaviours resulting from these strategies (eg, disruptive behaviour, truanting, not working hard) or the physical, social, or mental impacts of their school experiences (eg, hungry, tired, self-conscious, depressed) made it difficult to concentrate or participate in class, which in turn affected how they felt teachers viewed them. Interpretation: Engaging in negative behaviours to increase social acceptance or trying to be "invisible" in school might be key pathways through which higher bodyweight might negatively impact educational performance. Action to combat weight stigma, both within schools and in wider society, is urgently required and might help address these educational disparities. Funding: The Health Foundation.